2012
DOI: 10.1007/s13280-012-0304-3
|View full text |Cite
|
Sign up to set email alerts
|

Controls on Coarse Wood Decay in Temperate Tree Species: Birth of the LOGLIFE Experiment

Abstract: Dead wood provides a huge terrestrial carbon stock and a habitat to wide-ranging organisms during its decay. Our brief review highlights that, in order to understand environmental change impacts on these functions, we need to quantify the contributions of different interacting biotic and abiotic drivers to wood decomposition. LOG-LIFE is a new long-term 'common-garden' experiment to disentangle the effects of species' wood traits and siterelated environmental drivers on wood decomposition dynamics and its asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
150
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(161 citation statements)
references
References 73 publications
2
150
0
2
Order By: Relevance
“…Micro environmental conditions (temperature, water availability and gaseous regime) played a role, and likely influenced the composition of saproxylic fungi communities and respirational carbon loss [32]. Herrmann et al [7] also observed high variation in deadwood density within decay classes and hence only few significant differences between adjacent decay classes within a given species.…”
Section: Density Moisture and Tsd Charakteristics Of Decay Stagesmentioning
confidence: 99%
“…Micro environmental conditions (temperature, water availability and gaseous regime) played a role, and likely influenced the composition of saproxylic fungi communities and respirational carbon loss [32]. Herrmann et al [7] also observed high variation in deadwood density within decay classes and hence only few significant differences between adjacent decay classes within a given species.…”
Section: Density Moisture and Tsd Charakteristics Of Decay Stagesmentioning
confidence: 99%
“…However, it is often difficult to differentiate between the factors controlling the decay mechanisms (Cornelissen et al 2012, Risch et al 2013, Harmon et al 2013). Furthermore, due to the highly heterogeneous spatial distribution and its long-term decay dynamics, CWD is less represented in decomposition studies.…”
Section: ) Maymentioning
confidence: 99%
“…Decomposition of CWD is largely driven by microbial (mainly fungal) activity, which is influenced by substrate quality and environmental conditions (Harmon et al 1986). Disentangling the role of the different decomposition drivers is challenging because of their strong interactions (Cornelissen et al 2012). Lignin, cellulose and nitrogen (N) interactions seem to exert a major control on litter decomposition (Talbot & Treseder 2012).…”
Section: ) Maymentioning
confidence: 99%
“…Local-scale processes do affect wood decomposition where, for example, rates of mass loss depend on the species of wood-rot fungi and hyphal grazing by soil invertebrates 22,23 . The influence of these local-scale variables on wood decomposition at regional scales, relative to climate, is uncertain given the paucity of regional-scale wood decomposition studies 24 . Here we investigate whether climate or other factors primarily control wood decomposition rates across a regional gradient in temperate forest.…”
mentioning
confidence: 99%